Adsorption isotherm of densed monoclinic tungsten trioxide nanoparticles - Nandiyanto, Asep Bayu Dani; Ragadhita, Risti; Jumril Yunas (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study evaluated isotherm adsorption of densed monoclinic tungsten trioxide (WO3 ) nanoparticles. To ensure the prepared particles were dense, experiments were conducted by combining ball-milling process and calcination of ammonium pentahydrate powder, in which all experiments were done with no additional chemicals or solvents. The adsorption process was carried out by adsorbing curcumin (as a model of adsorbate) in the batch process at ambient temperature and constant pH and the results was compared to several isotherm models: Langmuir, Freundlich, Temkin and Dubinin-Radushkevich models. To support the analysis, several characterizations were conducted: scanning electron microscope, X-ray diffraction and Fourier transform infrared. Experimental results showed that during the adsorption process, physical and chemical interactions occur simultaneously. The physical interactions happen when the adsorbate molecules attach directly to the surface of the adsorbent, forming monolayer adsorption. The chemical interaction is for the interaction between adsorbate molecules and occurs on above the formed main monolayer adsorption. The results were also completed with the proposal mechanism in the adsorption process. This study is important for supporting the fundamental researches in the photochemical reaction using WO3 catalyst.